Pelaksanaan Pembelajaran Pendidikan Jasmani Adaptif di Panti Sosialg Bina Grahita (PSBG) Harapan Ibu Kalumbuk kota Padang - Chairunnas; Armaini (Attanwir : Jurnal Keislaman dan Pendidikan, 2020)
This studya aims too find oout how the implementationd of adaptive physical education learning in the social welfare building of bina grahita (pSbg) expectation of kalumbuk mothers in Padang. Thisi studyi used descriptive qualitativek method. The study was conducted in May 2019. Thea subjects of this studyi were adaptive longline teachers, principals, andi students. oData collection techniques using observation, interviews, pdocumentation, and oobservation. Data analysis techniques are data collection, odata reduction, datao display, andiconclusion/ verification. The results showed that thee formulation oof objectives was in accordance with tthe conditions of studentsd and the preparation in the learning device. Thei implementation has been going wello and in accordance with the theoryi even though the conditions of iadaptive teaching experience are stilla minimal in special schools. Evaluation of learningg is done attthe eend of each lesson, the rend of each pmaterial meeting, and aat the pend ofp each psemester. Thee follow up of the evaluation is the developmentt of movement for studentsi whose motor skills are pstill lacking and used as a referencer for padaptive physicali education teachersi forr future plearning.